Gestão de resíduos sólidos urbanos em municípios de pequeno porte: sistematização de diretrizes e procedimentos - Pellegrino, Stefânia Aparecida Custódio (Universidade Federal de São Carlos, 2003)
A new lifestyle, with changes in the consumption patterns and generation of residues, is imposed for humanity in Brazil, the growth of the cities and, at the same time, the increase in the consumption of industrialized products, are common factors to practically all the municipal districts. This way serious problems have been carted, regarding the inadequate administration of the urban solid residues (USW) generated. Because of its great number, the small municipal districts contribute with the current environmental and social problems. Thus, one of the main measures to be taken to correct this situation is the establishment of plans of the Management of USW (PMUSW) generated in such municipal districts. The present work lifted some concepts and administration models and management of USW, seeking to supply advices for the elaboration of PMUSW to small municipal districts, based in the minimization concepts. The small municipal districts can count with some facilities for an integrated administration of the different residues, especially the communication with the population, the inspection of the proposal measures, the organization of the society in the administration process of RSU. Besides, the amount of generated residues is smaller and the segregation process, collection and disposition can be simplified. On the other hand, such municipal districts face difficulties for the implantation of a good administration of USW, among them the lack of financial and human resources. Taking into account such characteristics, some guidelines were systematized and established some procedures that better adapt to the referred municipal districts, contemplating simplified solutions, of low cost, accessible to technicians and administrators without specialization in the theme and that involve the population. Such orientations were applied to a specific case of the small municipal district of (Itamogi-MG), allowing its evaluation by means of the elaboration of local PMUSW. In conclusion, it is possible to propose an administration of USW that assists the needs and limitations of those municipal districts.
Keywords: Resíduos sólidos; Gestão de resíduos sólidos; Municípios de pequeno porte; Minimização de resíduos; Lixo; Solids wastes; Solids Wastes management; Small municipal district; Minimization of wastes; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::RESIDUOS SOLIDOS, DOMESTICOS E INDUSTRIAIS